(untitled) (Journal of Oriental Studies, 2017)
This article investigates morphological ways of time constructions in Chagatay and Kipchak languages in comparative synchronic analysis. Also views of Russian and Turkish turkologists to forming, the development of these languages and their place in the classification of Turkic language are given.